Kenakalan Remaja: Faktor Penyebab, Akibat, dan Solusi - Shilphy (Yayasan Insanulhaq, 2025)
Juvenile delinquency is a fairly complex social problem and is often a major concern in society. Adolescence, which is a transition period from childhood to adulthood, is often marked by various physical, emotional, and social changes that affect individual behavior. Juvenile delinquency arises as a result of a combination of internal and external factors that encourage adolescents to commit deviant acts from social, legal, and religious norms. This study aims to explore the factors causing juvenile delinquency, its impacts, and solutions to overcome this problem. In this study, a qualitative approach was used by analyzing data obtained from various sources, including literature, interviews, and observations. It is hoped that this study can provide deeper insight into how to prevent and handle juvenile delinquency by involving the roles of family, school, community, and government.